IMPLEMENTATION OF SCALAR CONTROL METHOD FOR 3 PHASE INDUCTION MOTOR SPEED CONTROL - Prasetia, Abdul Muis; Santoso, Hadi (Elinvo (Electronics, Informatics, and Vocational Education), 2018)
This paper presents design and implementation of scalar control for 3 phase induction motor. This method leads to be able to adjust the speed of the motor by control the frequency and amplitude of the stator voltage of 3 phase induction motor, the ratio of stator voltage to frequency should be kept constant, which is called as V/F or scalar control of 3 phase induction motor drive. The proposed control system is used to generate control signals to overcome the nonlinear dynamics of 3 phase induction motor. Simulation results show that the 3 phase induction motor is able to track the frequency input shift via inverter with 50 Hz frequency get speed 2090.8 rpm.